Personal shopper (Jastip) and the representation of digital workers: A critical study of social media discourse in the gig economy - Elita Putri Pradipta; Taufiqur Rahman (Jurnal ASPIKOM - Jurnal Ilmu Komunikasi, 2025)
Personal shoppers (jastip) have emerged as informal digital workers within the gig economy, often promoted on social media as flexible and empowering entrepreneurial practices. However, behind this narrative lies a condition of precarity and limited labor protection. This study examines how the representation of jastip workers is discursively constructed on Instagram using Fairclough’s Critical Discourse Analysis. Adopting a critical qualitative approach, this research combines textual analysis, virtual ethnography, and interviews to analyze captions, visual elements, emojis, testimonials, and interaction patterns. The findings reveal that digital identity is constructed through affective language, visual consistency, and trust-oriented expressions, which serve as performative strategies to establish credibility. Participatory communication practices, such as live sessions and testimonial reposts, co-produce legitimacy while intensifying relational labor. At the level of social practice, these representations are embedded within the ideological logic of the gig economy and digital neoliberalism, where flexibility and productivity are emphasized while structural vulnerability remains obscured. This study highlights how platform logic and discourse shape trust, identity, and labor relations in informal digital work.